Digital Teaching Module on Teaching Practice Material Based on Value Clarification Technique (VCT) - Cyntiani Ratnaningsih, Made Nita; I Nyoman Laba Jayanta (Journal of Education Technology, 2023)
In the learning process, it is necessary to have learning resources that meet the needs of students like teaching modules. However, there are only several teaching modules can meet the learning needs, and there is no variation at all. By this phenomenom, a digital teaching module was developed on VCT-based teaching practice material for elementary Civics learning courses. It also completed with examples of teaching practices for VCT in Civics learning. This research used the ADDIE model. The subjects in this study were six experts. The data collection methods used were both interview and questionnaire methods. The results showed that the digital module on VCT teaching practice material for elementary civics learning courses obtained a material expert validity index of 95.95%, from media experts of 96% with a very good qualifications, and design experts of 92.5% with very good qualifications. The average value of the teaching module practitioners obtained 98.65% with a very good qualifications, the average value of the individual test was 95% with a very qualifications, and the average value of the small group test was 97.7% with a very good qualifications. So, it is concluded that the development of digital teaching modules on teaching practice material based on the Value Clarification Technique (VCT) for elementary civics learning courses is declared valid and practical to be applied as a guide for elementary civics learning courses.